(untitled) (CIPEEX, 2025)
OBJECTIVE: To analyze the spatial distribution of Hepatitis B and C cases in the municipality of Anápolis, Goiás. METHOD: A quantitative, descriptive, observational, and cross-sectional study was conducted using secondary data provided by the Anápolis Health Department. Geographical and temporal patterns were described with the aim of guiding more effective public health strategies. RESULTS: Central neighborhoods and the northern zone of Anápolis, such as Centro, Jaiara, and Jardim América, had high incidences of both infections, suggesting areas of greater vulnerability and in need of specific preventive measures. CONCLUSION: To reduce the incidence of hepatitis B and C in Anápolis, it is crucial to implement public health policies that include awareness campaigns, vaccination, and improvements in access to diagnostic and treatment services, especially in the most affected areas. These actions can help control the transmission of infections and improve the health of the local population.